2006
DOI: 10.1364/ao.45.008839
|View full text |Cite
|
Sign up to set email alerts
|

Grinding surface roughness measurement based on the co-occurrence matrix of speckle pattern texture

Abstract: Surface speckle pattern intensity distribution resulting from laser light scattering from a rough surface contains various information about the surface geometrical and physical properties. A surface roughness measurement technique based on the texture analysis of surface speckle pattern texture images is put forward. In the surface roughness measurement technique, the speckle pattern texture images are taken by a simple setup configuration consisting of a laser and a CCD camera. Our experimental results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…the grey-level co-occurrence matrix (GLCM), which deals with spatial relationships of pairs of grey-value pixels (Haralick et al, 1973). Previously, GLCM was applied to retrieving surface roughness from laser speckle images (Lu et al, 2006). Initially, four GLCM features were chosen: contrast, correlation, energy and homogeneity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the grey-level co-occurrence matrix (GLCM), which deals with spatial relationships of pairs of grey-value pixels (Haralick et al, 1973). Previously, GLCM was applied to retrieving surface roughness from laser speckle images (Lu et al, 2006). Initially, four GLCM features were chosen: contrast, correlation, energy and homogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…It is relevant that the GLCM energy also shows good correlation with roughness in the context of laser speckle from flat surfaces, and is most robust with respect to variation of "the setup configuration, the position, and the orientation of the surface to be measured" (Lu et al, 2006). So only this GLCM feature is reported henceforth.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal complexity analysis relies on the grey-level cooccurrence matrix (GLCM) method described in Lu et al (2006). This method was originally developed in the context of quality control of surface treatment processes, and Ulanowski et al (2010) transferred it for the first time to the analysis of SID-3 ice crystal scattering patterns.…”
Section: Scattering Pattern Analysismentioning
confidence: 99%
“…Xie [24] concluded that statistical and filter based approaches are those most widely applied. Attempts have been made to find correlations between features in images and the surface properties of manufactured components, such as roughness [27], [28], [29]. Others have analyzed tool wear [30] and the rugosity of metal parts [31].…”
Section: Literature Reviewmentioning
confidence: 99%